Whole genome sequencing of Caribbean Hispanic families with late-onset Alzheimer's disease. - Vardarajan, Badri N; Barral, Sandra; Jaworski, James; Beecham, Gary W; Blue, Elizabeth; Tosto, Giuseppe; Reyes-Dumeyer, Dolly; Medrano, Martin; Lantigua, Rafael; Naj, Adam; Thornton, Timothy; DeStefano, Anita; et al. (Ann Clin Transl Neurol, 2018)
Objective: To identify rare causal variants underlying known loci that segregate with late-onset Alzheimer's disease (LOAD) in multiplex families. Methods: We analyzed whole genome sequences (WGS) from 351 members of 67 Caribbean Hispanic (CH) families from Dominican Republic and New York multiply affected by LOAD. Members of 67 CH and additional 47 Caucasian families underwent WGS as a part of the Alzheimer's Disease Sequencing Project (ADSP). All members of 67 CH families, an additional 48 CH families and an independent CH case-control cohort were subsequently genotyped for validation. Patients met criteria for LOAD, and controls were determined to be dementia free. We investigated rare variants segregating within families and gene-based associations with disease within LOAD GWAS loci. Results: A variant in p.R434W, segregated significantly with LOAD in two large families (OR = 5.77, 95% CI: 1.07-30.9, = 0.041). In addition, missense mutations in and under previously reported linkage peaks at 7q14.3 and 11q12.3 segregated completely in one family and in follow-up genotyping both were nominally significant ( < 0.05). We also identified rare variants in a number of genes associated with LOAD in prior genome wide association studies, including ( = 0.049), ( = 0.0098) and ( = 0.040). Conclusions and Relevance: Rare variants in multiple genes influence the risk of LOAD disease in multiplex families. These results suggest that rare variants may underlie loci identified in genome wide association studies.

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins